The correlation between the daily incidence of varicella and meteorological factors in Jiangxi province from 2015 to 2021: a surveillance data analysis - Xing YE; Chengfeng ZHANG; Huijian CHENG; Sheng DING; Weijie FU (Zhongguo gonggong weisheng, 2025)
ObjectiveTo understand the correlation between the incidence of varicella and meteorological factors in Jiangxi province from 2015 to 2021, and to provide a reference for meteorological prediction and early warning of varicella incidence. MethodsDaily varicella incidence data reported by direct reporting units for infectious diseases in Jiangxi province from January 1, 2015, to December 31, 2021, were collected from the Chinese Center for Disease Control and Prevention Information System. Meteorological data for the same period, including daily minimum temperature, daily maximum temperature, daily average temperature, sunshine duration, daily maximum wind speed, daily precipitation, and daily average relative humidity, were collected from the Jiangxi Meteorological Bureau. Pearson correlation analysis and generalized linear regression models were used to analyze the relationship between varicella incidence and different meteorological factors in Jiangxi province. ResultsA total of 133 370 varicella cases were reported in Jiangxi province from 2015 to 2021, with a daily incidence of (51 ± 36) cases. Among these cases, 31 604 (23.70%) were in the 0 - 4 age group, 26 910 (20.18%) were in the 5 - 9 age group, 45 938 (34.44%) were in the 10 - 14 age group, and 28 918 (21.68%) were in the ≥ 15 age group. Pearson correlation analysis showed that the daily incidence of varicella was negatively correlated with daily minimum temperature (r = -0.280, P < 0.001), daily maximum temperature (r = -0.270, P < 0.001), daily average temperature (r = -0.280, P < 0.001), sunshine duration (r = -0.079, P < 0.001), daily maximum wind speed (r = -0.130, P < 0.001), and daily precipitation (r = -0.093, P < 0.001). Generalized linear regression analysis showed that the daily incidence of varicella in the 0 - 4 and 5 - 9 age groups was negatively correlated with daily average temperature (β = -0.032 and -0.027, both P < 0.001) and daily maximum wind speed (β = -0.004 and -0.062, both P < 0.05). The daily incidence of varicella in the 10 - 14 and ≥ 15 age groups was negatively correlated with daily average temperature (β = -0.022 and -0.024, both P < 0.001) and daily precipitation (β = -0.007 and -0.007, both P < 0.05). ConclusionsThere was a significant negative correlation between the incidence of varicella and various meteorological factors, including daily minimum temperature, daily maximum temperature, daily average temperature, sunshine duration, daily maximum wind speed, and daily precipitation, in Jiangxi province from 2015 to 2021. The correlation between the daily incidence of varicella and meteorological factors varied across different age groups.